Evidence that Marine Temperatures Influence Growth and Maturation of Western Alaskan Chinook Salmon. Issue 1 (1st January 2017) - Siegel, Jared E.; McPhee, Megan V.; Adkison, Milo D.
Abstract: Chinook Salmon Oncorhynchus tshawytscha from western Alaska have experienced recent declines in abundance, size, and age at maturity. Declines have led to hardships for the region's subsistence and commercial salmon harvesters, prompting calls to better understand factors affecting the life history of these populations. Western Alaskan Chinook Salmon are thought to spend their entire marine residency in the Bering Sea. The Bering Sea ecosystem demonstrates high interannual variability that is largely driven by the annual extent of sea ice. However, warming is expected to supersede interannual variability in the next several decades as a consequence of climate change. We investigated the influence of sea surface temperatures (SSTs) on the life history of western Alaskan Chinook Salmon by using information from two regional populations subject to long-term monitoring. We found strong correlations between early marine growth and SSTs. Warmer SSTs appeared to lead to a younger age at maturity, largely through the vector of augmented growth. However, we also present evidence that warmer SSTs may additionally decrease the average age of male recruits through reduced growth thresholds for early male maturation. Our results suggest that the anticipated warming of the Bering Sea will lead to higher early marine growth and a younger average age of maturation for western Alaskan Chinook Salmon. Received March 30, 2017; accepted July 4, 2017